KEUNGGULAN KOMPETITIF GULA CAIR KIMPUL - Rejeki, Fungki Sri; Puspitasari, Diana; Wedowati, Endang Retno (Journal of Research and Technology, 2017)
The need of sugar as a sweetener is increasing, therefore it needs to look for other alternative sweeteners by developing liquid sugar from starch. Purse as one type of potential root crops have a great opportunity to be developed because it contains a high carbohydrate. The purpose of this research is to determine the best process of purse liquid sugar with acid and enzyme hydrolysis. This research consists of two stages. The first stage is the optimization process using acid hydrolysis and the second stage is the optimization process using enzyme hydrolysis. The tested parameters are Brix, moisture content, ash content, and reducing sugar. The best alternative process is based on Value Expectations Method. Furthermore, the products are tested for caloric value and Glycemic Index (GI). The results shows: (1) The best of acid hydrolysis process is adding 15 ml acid with hydrolysis time 1 hour, which produces purse liquid sugar with 86.30% moisture content, 2,01% ash content, 13,33oBrix, 10,21% reducing sugar, 41 calories and GI value is 47,32; (2) The best of enzyme hydrolysis process is adding 3 ml enzyme and hydrolysis temperature of 100oC, which produces purse liquid sugar with 73.73% moisture content, 0.24% ash content, 25.17oBrix, 23,43% reducing sugar, 106 calories and GI value is 80.63. Keywords: Optimization Process, Hydrolysis, Liquid Sugar, Purse.